2012
DOI: 10.1007/s11548-011-0669-y
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection and classification of nasopharyngeal carcinoma on PET/CT with support vector machine

Abstract: Purpose Positron emission tomography/computed tomography (PET/CT) has established values for imaging of head and neck cancers, including the nasopharyngeal carcinoma (NPC), utilizing both morphologic and functional information. In this paper, we introduce a computerized system for automatic detection of NPC, targeting both the primary tumor and regional nodal metastasis, on PET/CT. Methods Candidate lesions were extracted based on the features from both PET and CT images and a priori knowledge of anatomical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Amongst these, nine studies focussed on the assessment of oral squamous cell carcinoma (OSCC) and seven studies focussed on the evaluation of, or differentiation between, oral potentially malignant disorders (OPMD) and OSCC. The remaining studies focussed on assessment of nasopharyngeal SCC ( n = 3), 29 31 laryngeal SCC ( n = 2), 32 , 33 oropharyngeal SCC ( n = 3), 34 36 parotid gland neoplasms ( n = 2) 37 , 38 and differentiation between sinonasal SCC from inverted papilloma ( n = 1). 39 In four studies, 40 42 tissue sections of HNC from various different sites (tongue, floor of mouth, soft palate, mandible, gingivae, alveolar ridge, supraglottis, maxillary sinus, nose, thyroid and parotid gland) were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst these, nine studies focussed on the assessment of oral squamous cell carcinoma (OSCC) and seven studies focussed on the evaluation of, or differentiation between, oral potentially malignant disorders (OPMD) and OSCC. The remaining studies focussed on assessment of nasopharyngeal SCC ( n = 3), 29 31 laryngeal SCC ( n = 2), 32 , 33 oropharyngeal SCC ( n = 3), 34 36 parotid gland neoplasms ( n = 2) 37 , 38 and differentiation between sinonasal SCC from inverted papilloma ( n = 1). 39 In four studies, 40 42 tissue sections of HNC from various different sites (tongue, floor of mouth, soft palate, mandible, gingivae, alveolar ridge, supraglottis, maxillary sinus, nose, thyroid and parotid gland) were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, support vector machine (SVM) and neural network have been widely utilized in learning-based methods. Wu et al [13] developed an automatic algorithm for detecting NPC lesions on PET-CT images with SVM. Mohammed et al [14] implemented automatic segmentation and identification of NPC by using artificial neural network in microscopy images to identify preliminary NPC cases.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative studies exist which tackle the challenge of automatically discriminating between normal and pathological tissues in PET. Unfortunately, a full comparison of such algorithms is not possible as the relative studies often concern different body district and specific types of abnormality, e.g., lung tumours [40][41][42], oesophageal tumours [43], and nasopharyngeal tumours [44]. Studies on discrimination of pathological structures in whole-body PET have been conducted as well, and some preliminary results have shown that different anatomical areas pose different challenges [45,46].…”
Section: Introductionmentioning
confidence: 99%